Keterampilan Guru dalam Membangkitkan Semangat AUD Ketika Memulai Pembelajaran - Nur Maulida; Tria Mayanjani; Ulfa Kiranti; Nur Afifa Daulay; Sahri Wulandari; Fauziah Nasution (Journal on Education, 2023)
Teacher skills are needed to enliven the learning atmosphere in the classroom and success in conducting learning. If the teacher is less skilled and creative in arousing student motivation when starting learning, then the child will feel bored and bored when the teaching and learning process is carried out. Therefore, teachers are required to always be able to arouse AUD enthusiasm when starting learning. The research method used is descriptive qualitative. Where this research uses library research (library research). So before starting the lesson the teacher must provide enthusiasm and motivation such as praying, ice breaking, wishing to give rewards when learning is over, and so on.